1997
DOI: 10.1002/(sici)1097-4628(19970815)65:7<1395::aid-app18>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Cell distributions in and sound absorption characteristics of flexible polyurethane foams

Abstract: In this article, the two-dimensional distributions of cells from the cross section of some flexible polyurethane foams were cleared, and the three-dimensional distributions of cells based on Saltykov's theory were estimated further. As a result, it was found that a mean of the two-dimensional distributions of cells was a good linear relation with a mean of the three-dimensional distributions of cells, and it was confirmed that cell structure of the foams which should have been analyzed in the threedimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Regarding the influence of the cell characteristics, the sound absorption characteristics of flexible polyurethane foams were investigated by Adachi et al [19]; the focus of that study was related to the influence of two-dimensional and three-dimensional cell distribution. Optimizing open-cells and air saturated polymer foams for acoustical and vibrational performance was studied by Nordgren and Göransson [20]; the aim of this work was to establish a porous cell methodology to estimate the acoustic behavior of porous foam as well as to explore the possibilities to optimize this behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the influence of the cell characteristics, the sound absorption characteristics of flexible polyurethane foams were investigated by Adachi et al [19]; the focus of that study was related to the influence of two-dimensional and three-dimensional cell distribution. Optimizing open-cells and air saturated polymer foams for acoustical and vibrational performance was studied by Nordgren and Göransson [20]; the aim of this work was to establish a porous cell methodology to estimate the acoustic behavior of porous foam as well as to explore the possibilities to optimize this behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement is rather large, with an increase in from 0.54 to 0.74 when adding 10% HBP at 800 Hz. There have been attempts to correlate to the modulus of the material [16] but the trends have been rather weak. For the materials in this present study, trends of increasing acoustic damping with increasing modulus can be found for certain frequency ranges.…”
Section: Acoustic Dampingmentioning
confidence: 99%
“…Vibration characteristics of flexible PU foams for automotive seating have been explored by applying an accelerating force on the seat cushion and measuring the transmissivity or transfer function as a function of frequency [13,14]. For investigation of the acoustic damping properties in the higher frequency range, normal incident sound absorption coefficients for flexible PU foams have been studied with the impedance tube technique [12,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, the studies on PU foam focus on the influence of pore sizes, pore structures, and material intrinsic parameters on the acoustic properties and sound waves transmission mechanism of materials 13–17 . Adachi et al 18 investigated the two‐dimensional distributions of cells from the cross section and three‐dimensional distributions of cells of polyester‐based flexible PU foams. Their analysis showed that the cell number, cell distribution, and cell diameter all have important effects on the sound absorption properties of PU foams.…”
Section: Introductionmentioning
confidence: 99%
“…Although PU foam has been applied in the field of acoustic materials, the inhomogeneous size and distribution of its internal pores limit its application fields 18,21,31,32 . However, metallic hollow spheres developed in recent years are a relative controllable cavity material with size and distribution, which can solve the above shortcomings of PU foam.…”
Section: Introductionmentioning
confidence: 99%